Addressing critical limitations of oyster (Ostrea edulis) restoration: Identification of nature‐based substrates for hatchery production and recruitment in the field. Issue 11 (12th November 2020) - Colsoul, Bérenger; Pouvreau, Stéphane; Di Poi, Carole; Pouil, Simon; Merk, Verena; Peter, Corina; Boersma, Maarten; Pogoda, Bernadette
Abstract: The European flat oyster ( Ostrea edulis ) is an ecosystem engineer that provides important biogenic reef habitat with associated ecosystem functions and services. Most stocks have been commercially exploited and degraded; some are functionally extinct. Ecological restoration now aims to recover these degraded, damaged or destroyed ecosystems. Availability of seed oysters and substrate for successful larval recruitment has been identified as a major limiting factor for restoration projects in Europe. In substrate‐limited areas, restoration approaches have to involve the restoration of suitable substrates. The present study provides an evaluation of such potential substrate types. Various categories were investigated through hatchery and/or field experiments: (1) marine bivalve shells; (2) inorganic materials; (3) sandy sediment; (4) 3D sandstone reefs; (5) wood materials; and (6) limed materials. The respective settlement rates (settled larvae per cm 2 ) indicate settlement preferences. Hatchery experiments showed significant preferences for bivalve shells and inorganic materials. Best settlement rates were observed on Mytilus edulis shells, followed by O . edulis shells as well as on slaked lime and on baked clay. Settlement was significantly higher on bottom‐oriented areas of bivalve shells and 3D reefs in laboratory experiments; however, this was not substantiated in the field experiments. Field experiments showed significant settlement preferences between substrate categories (bivalve shells, inorganic materials and wood materials). Best settlement rates were observed on baked clay, followed by slaked lime and bivalve shells. Wooden materials did not perform. Settlement rates and substrate preferences of larvae in controlled environments (laboratory, hatchery) differed from rates in the natural environment (field). This study provides a list of substrate types considering these specific environments. The relevance of these results for ecological restoration in the field and potential applications in seed oyster production are discussed.